Information-seeking behaviour and the use of electronic information resources among undergraduate students: a systematic literature review - Ahmed, Mohammed Bello; Wan Mokhtar, Wan Nor Haliza; Baharuddin, Mohammad Fazli (Faculty of Information Management, 2025)
Nowadays it is a prerequisite for libraries to understand their users' information-seeking behaviour and tailor their services to meet these needs. This study aims to explore information-seeking behaviour (ISB) and electronic information resources (EIRs) for academic pursuits, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. Moreover, it seeks to offer valuable insights that will enhance EIRs, library resources, innovative pedagogies, and technological support for librarians, educators, and policymakers. It also strives to foster novel knowledge that will propel future research inquiries and support universities' missions of producing high-calibre skilled graduates who are capable in efficiently managing the nation's labour cycle. The study will gather data by searching four electronic databases: EBSCO, Google, Scopus, and ProQuest, for peer-reviewed articles published between 2022 and 2024. It will search certain (000) research articles for the review. The review covers qualitative, quantitative, and mixed studies conducted across educational institutions, such as universities, colleges, and technical institutions. This hopes to uncover numerous factors that can impact students' academic pursuits. It provides conclusions and recommendations.